AUTOMATED PUPILLOMETRY FOR PREDICTION OF SPACE-OCCUPYING HEMISPHERIC INFARCTION AFTER ENDOVASCULAR TREATMENT - Köhn, Julia; Kobus, Franca; Kossel, Clara-Sophie; Borutta, Matthias; Kuramatsu, Joji; Schwab, Stefan (JOURNAL OF NEUROTRAUMA, 2022)
CRIS-Team WoS Importer:2022-09-02

Correction of Vertebral Bone Development in Ectodysplasin A1-Deficient Mice by Prenatal Treatment With a Replacement Protein - Kossel, Clara-Sophie; Wahlbuhl-Becker, Mandy; Schuepbach-Mallepell, Sonia; Park, Jung; Kowalczyk-Quintas, Christine; Seeling, Michaela; von der Mark, Klaus; Schneider, Pascal; Schneider, Holm (Frontiers in Genetics, 2021)
X-linked hypohidrotic ectodermal dysplasia with the cardinal symptoms hypodontia, hypotrichosis and hypohidrosis is caused by a genetic deficiency of ectodysplasin A1 (EDA1). Prenatal EDA1 replacement can rescue the development of skin appendages and teeth. Tabby mice, a natural animal model of EDA1 deficiency, additionally feature a striking kink of the tail, the cause of which has remained unclear. We studied the origin of this phenomenon and its response to prenatal therapy. Alterations in the distal spine could be noticed soon after birth, and kinks were present in all Tabby mice by the age of 4 months. Although their vertebral bones frequently had a disorganized epiphyseal zone possibly predisposing to fractures, cortical bone density was only reduced in vertebrae of older Tabby mice and even increased in their tibiae. Different availability of osteoclasts in the spine, which may affect bone density, was ruled out by osteoclast staining. The absence of hair follicles, a well-known niche of epidermal stem cells, and much lower bromodeoxyuridine uptake in the tail skin of 9-day-old Tabby mice rather suggest the kink being due to a skin proliferation defect that prevents the skin from growing as fast as the skeleton, so that caudal vertebrae may be squeezed and bent by a lack of skin. Early postnatal treatment with EDA1 leading to delayed hair follicle formation attenuated the kink, but did not prevent it. Tabby mice born after prenatal administration of EDA1, however, showed normal tail skin proliferation, no signs of kinking and, interestingly, a normalized vertebral bone density. Thus, our data prove the causal relationship between EDA1 deficiency and kinky tails and indicate that hair follicles are required for murine tail skin to grow fast enough. Disturbed bone development appears to be partially pre-determined in utero and can be counteracted by timely EDA1 replacement, pointing to a role of EDA1 also in osteogenesis.
CRIS-Team Scopus Importer:2021-09-10
Keywords: bone; development; ectodermal dysplasia; ectodysplasin A1; fetal therapy; NF-κB

Pupillometry in the follow-up of patients undergoing EVT - prediction of space-occupying hemispheric infarction - Kossel, Clara-Sophie; Kobus, Franca; Borutta, Matthias; Kärtner, Maximilian; Kuramatsu, Joji; Engelhorn, Tobias; Schwab, Stefan; Köhn, Julia (Journal of Neurology, 2023)
Background: Despite benefits of endovascular treatment (EVT) for large vessel occlusion (LVO) ischemic stroke, space-occupying brain edema (BE) represents a detrimental complication. In critical-care settings, CT-imaging is needed for monitoring these patients. Yet, bed-side techniques with the potential to predict whether patients develop BE or not would facilitate a time- and cost-efficient patient care. We assessed clinical significance of automated pupillometry in the follow-up of patients undergoing EVT. Methods: From 10/2018 to 10/2021, neurocritical-care-unit patients were retrospectively enrolled after EVT of anterior circulation LVO. We monitored parameters of pupillary reactivity [light-reflex-latency (Lat), constriction- and redilation-velocities (CV, DV), percentage-change-of-apertures (per-change); NeurOptics-pupilometer®] up to every hour on day 1–3 of ICU stay. BE was defined as midline shift ≥ 5 mm on follow-up imaging 3–5 days after EVT. We calculated mean values of intra-individual differences between successive pairs of parameters (mean-deltas), determined best discriminative cut-off values for BE development (ROC-analyses), and evaluated prognostic performance of pupillometry for BE development (sensitivity/specificity/positive-/negative-predictive-values). Results: 3241 pupillary assessments of 122 patients [67 women, 73 years (61.0–85.0)] were included. 13/122 patients developed BE. Patients with BE had significantly lower CVs, DVs, and smaller per-changes than patients without BE. On day 1 after EVT mean-deltas of CV, DV, and per-changes were significantly lower in patients with than without BE. Positive-predictive-values of calculated thresholds to discriminate both groups were considerably low, yet, we found high negative-predictive-values for CV, DV, per-changes, and mean-deltas (max.: 98.4%). Conclusion: Our data suggest associations between noninvasively detected changes in pupillary reactivity and BE early after LVO-EVT. Pupillometry may identify patients who are unlikely to develop BE and may not need repetitive follow-up-imaging or rescue-therapy.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Automated pupillometry; Endovascular treatment; Ischemic stroke; Large vessel occlusion; Pupillary reactivity